2020
DOI: 10.1017/s0022029920000618
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress in dairy calves from birth to weaning

Abstract: This Research Reflection collects current knowledge on the effects of heat stress in dairy calves. Chapters cover the concept of foetal programming, animal-based and environmental indicators of heat stress in the postnatal period, and methods of heat stress abatement. Conclusions for further research about economic efficiency, research methodology and an integrated approach of pre- and postnatal heat stress are also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In the present study, maternal heat stress during late gestation decreases BW by up to 570 days of age in SB3 group heifers born between July and September. These results corroborated those of other authors [68,69,[72][73][74][75][76][77] and confirm that a calf body weight can be significantly impacted by heat stress during the final weeks of gestation. However, what about the SB4 group?…”
Section: Season Of Birth and Father's Lineage Factors (Sb F)supporting
confidence: 92%
“…In the present study, maternal heat stress during late gestation decreases BW by up to 570 days of age in SB3 group heifers born between July and September. These results corroborated those of other authors [68,69,[72][73][74][75][76][77] and confirm that a calf body weight can be significantly impacted by heat stress during the final weeks of gestation. However, what about the SB4 group?…”
Section: Season Of Birth and Father's Lineage Factors (Sb F)supporting
confidence: 92%
“…Also, Shivley et al (2018) reported that calves experiencing high temperature-humidity indices (50 to 69 and >70) grew at a slower rate than calves in a cooler climate, suggesting that heat stress may have a negative effect on ADG and, potentially, DFI. Others (Bakony and Jurkovich, 2020;Dado-Senn et al, 2020;Wang et al, 2020) have indicated that postnatal heat stress reduces feed intake in young calves.…”
Section: Discussionmentioning
confidence: 99%
“…1 With climate change and the global temperature increasing, the negative impacts of heat stress on dairy animals have increased. 1,2 Heat stress occurs when dairy animals generate and absorb more heat than they can get rid of by normal physiological activities, such as respiration, sweating, and air blowing. 2,3 Under heat stress conditions, dairy animals exhibit increases in heart rate, respiration, and rectal temperature and reductions in feed intake, both of them exerting negative impacts on milk performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Heat stress caused by high temperatures greatly decreases the milk production of dairy animals and results in considerable economic loss to dairy farmers . With climate change and the global temperature increasing, the negative impacts of heat stress on dairy animals have increased. , Heat stress occurs when dairy animals generate and absorb more heat than they can get rid of by normal physiological activities, such as respiration, sweating, and air blowing. , Under heat stress conditions, dairy animals exhibit increases in heart rate, respiration, and rectal temperature and reductions in feed intake, both of them exerting negative impacts on milk performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation